2006
DOI: 10.1051/0004-6361:20053948
|View full text |Cite
|
Sign up to set email alerts
|

Abundance studies of sdB stars using UV echelle HST/STIS spectroscopy

Abstract: Aims. We test the hypothesis that the pulsations in sdB stars are correlated with the surface abundances of iron-group elements. Any correlation might explain why, when given two spectroscopically similar stars, one will pulsate while the other will not. Methods. We have obtained high-resolution ultraviolet spectra two pulsating and three non-pulsating sdB stars using the Space Telescope Imaging Spectrograph onboard the Hubble Space Telescope. We determined abundances for 25 elements including the iron group a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 27 publications
12
98
0
Order By: Relevance
“…Since the C ii/C iii abundances given in literature O'Toole & Heber 2006) do not show such high deviations, we conclude that the limited number of lines used in our study leads to those systematic shifts. Especially the C ii lines at 4267 Å are known to be very sensitive to NLTE effects (Nieva & Przybilla 2008).…”
Section: Comparison With Literature and Systematic Uncertaintiesmentioning
confidence: 47%
See 2 more Smart Citations
“…Since the C ii/C iii abundances given in literature O'Toole & Heber 2006) do not show such high deviations, we conclude that the limited number of lines used in our study leads to those systematic shifts. Especially the C ii lines at 4267 Å are known to be very sensitive to NLTE effects (Nieva & Przybilla 2008).…”
Section: Comparison With Literature and Systematic Uncertaintiesmentioning
confidence: 47%
“…However, the abundance patterns of pulsating sdBs turned out to be the same as the ones of non-pulsating comparison stars with similar atmospheric parameters (Heber et al 2000;O'Toole & Heber 2006;Blanchette et al 2008).…”
Section: Abundance Patterns Of Sdb Sub-populationsmentioning
confidence: 85%
See 1 more Smart Citation
“…In [4], the Ar III λ = 1002.097 Å spectral line has been used in the determination of abundance in hydrogen-rich subdwarf B stars. Ar III spectral lines were also observed by O'Toole and Heber [5] in the spectra of subdwarf B stars. Based on lines of Ar II, Heber and Edelmann [6] have reported abundances of argon in B subdwarfs.…”
Section: Introductionmentioning
confidence: 53%
“…The chemical composition of sdB stars is known to be highly peculiar, showing large deficiencies for the lighter elements (e.g. C and Si) on the one hand, and strong overabundances of heavy elements as deduced from UV and FUV spectra on the other (see O'Toole & Heber 2006;Blanchette et al 2008), while iron is found to be approximately solar in most sdBs. The line blocking of UV iron lines is responsible for most of the line blanketing affecting the temperature-density stratification of the model atmosphere.…”
Section: Computation Of Synthetic Line-profile Variationsmentioning
confidence: 99%